The Impact of the COVID-19 Pandemic on Mobility Trends and the Associated Rise in Population-Level Physical Inactivity: Insights From International Mobile Phone and National Survey Data - Dobbie, Laurence J.; Hydes, Theresa J.; Alam, Uazman; Tahrani, Abd; Cuthbertson, Daniel J. (Frontiers in Sports and Active Living, 2022)
Introduction The COVID-19 pandemic has reduced physical activity (PA) levels. This is important as physical inactivity is linked to poor COVID-19 outcomes. This study aimed to assess the impact of COVID-19 pandemic restrictions on greenspace and residence mobility, walking levels and in turn how these translated to trends in (UK) PA levels. Methods Google Mobility Reports, the Oxford COVID-19 Government Response Tracker and Apple Mobility geospatial datasets were interrogated for international data. Residence mobility represents home mobility, greenspace mobility includes parks, walking direction requests is proportion of walking directions; stringency index measures lockdown intensity. The Sports England Active Lives Survey dataset was assessed for complementary changes in English PA levels. Results Using mobility data of 10 countries we observed that during lockdown there were reductions in greenspace mobility and walking directions alongside increased residence mobility; more pronounced changes were seen in countries with higher stringency indices. From a UK perspective, complementary English PA survey data demonstrated the impact of these mobility changes on the proportion and demographic characteristics of PA levels. The most vulnerable in society, the elderly (ages 75+) and Black and Asian minority ethnicity (BAME) individuals were more likely to become physically inactive. Conclusions The COVID-19 pandemic globally reduced greenspace mobility and walking direction requests. Complementary assessment of English PA levels demonstrated a greater proportion of the population became inactive. Demographics (75+ and BAME) prone to worse COVID-19 outcomes became disproportionately inactive. UK Urban planning should prioritise greenspace development. This could improve city walkability and PA levels.